(untitled) (Heritage, 2021)
Ultimately, this article should not be taken as an appeal against a Latin letter, nor should the author’s intention to ban or restrict the use of this letter. The main goal is that the Latin letter in the areas where the Serbian people live cannot be primary, but should be used only as required by the Serbian Constitution, as well as the still applicable Law on the Official Use of Languages and Letters in the Republic of Serbia. Giving up your own letter (Cyrillic) is a sign of the lack of awareness of the need to nurture its own cultural values, preserve national identity and its characteristics. It also points to a lower-value complex and a misconception that moving away from ourselves will bring us closer to others. One should also remember the words of our writer Laze M. Kostic that "with the emergence of Cyrillic, Serbs were culturally created, with its renunciation they would culturally disappear. They would cease to exist as an independent nation, an independent cultural individuality." Neither will the laws of Cyrillic or not sufficiently and desirablely, unless we just change our awareness of it. Only in this way can we correct the mistakes of the not-so-distant past (from the second half of the 20th century), and learn the not to give up Cyrillic for any purposes, ideals, possibly future state unions and the aforementioned brotherhood and unity.